Underrepresentation of Minoritized Groups in STEM Education: The Development of a Survey - Kate Neally (Journal of Interdisciplinary Studies in Education, 2023)
The current school system has an underrepresentation of People of Color teaching science, technology, engineering, and mathematics (STEM). Presently, there is a lack of data gathering tools to explore the STEM experience of Students of Color. This article focuses on the development of a survey using a Critical Race Theory framework to better understand the impact of race on the STEM education pipeline for underrepresented, racially minoritized (URM) learners. This article will review the survey’s development process consisting of (a) creation of initial survey; (b) pilot study using interviews to receive feedback; (c) modifying the survey based on the feedback from the pilot study; and (d) implementation of the revised survey. Ultimately this instrument will support inquiry around racial representation in STEM education.